Cardiac Echinoccocosis and Morbid Obesity. Surgical Considerations - Ramírez Ramírez, José Alfredo (2010)
We report the case of a 49-year-old patient with morbid obesity in whom a hydatid cyst in the left ventricle was detected by means of a thoracic CT scan. The cyst was excised through a left submammary thoracothomy without using extracorporeal circulation. Pathological anatomy studies evidenced the presence of scolices on the hydatid membrane. After being followed-up for one year, the patient does not have any cardiac-respiratory symptom, and there is no evidence of cardio-thoracic hydatidosis.